Study of the bioindicative role of the springtail in the urban soil environment and possibilities to use them in practice - Tien, Nguyen Tri; Thanh, Duong Thi (Academia Journal of Biology, 2015)
Investigations and collections of the springtail were carried out in 10 cities and towns of the Red river delta from 1998 until now. Basing on the analysis of the changes on quality quantitative index of the springtail (species quality, density, diversity index, dominant structure,...) under the human effect, the authors concluded that the springtail can be used as a tool to monitor and to estimate the soil quality, to foresee the tendency influencing on the soil environment of external factors, especially the human activity intervening the soil environment.